Lung adenocarcinoma and colorectal cancer as double primary malignancies reveal lynch syndrome: a case report of germline MLH1 mutation with response to immunotherapy and familial aggregation - Wang, Menglei; Xue, Haoyue; Hong, Jiamin; Liu, Qi; Hu, Keke; Shu, Chang; Wang, Jinghua; Long, Yu; Han, Yehong; Yang, Xuefei; Lu, Jinhua (Frontiers in Immunology, 2026)
Lynch syndrome (LS), also known as hereditary nonpolyposis colorectal cancer, is a genetic condition that increases the risk of developing colorectal cancer (CRC) and other cancers due to defective DNA mismatch repair (dMMR). This article reports a case of a patient who developed lung adenocarcinoma followed by CRC. The detection of dMMR by immunohistochemistry in both the metastatic lesion and CRC led to retrospective testing, which revealed a concomitant loss of MLH1 and PMS2 in the primary lung cancer. Germline testing subsequently confirmed a diagnosis of LS associated with an MLH1 mutation, with significant familial clustering observed. The patient responded effectively to anti-PD-1 immunotherapy. This case highlights that lung adenocarcinoma can be a manifestation of LS and underscores the critical importance of retrospective MMR testing in establishing the diagnosis. Furthermore, it demonstrates the efficacy of immune checkpoint inhibitions in advanced dMMR tumors.